Prenylated flavonoids with potential antimicrobial activity: synthesis, biological activity, and in silico study - Osorio, Mauricio (2021)
Prenylated flavonoids are an important class of naturally occurring flavonoids with important biological activity, but their low abundance in nature limits their application in medicines. Here, we showed the hemisynthesis and the determination of various biological activities of seven prenylated flavonoids, named 7–13, with an emphasis on antimicrobial ones. Compounds 9, 11, and 12 showed inhibitory activity against human pathogenic fungi. Compounds 11, 12 (flavanones) and 13 (isoflavone) were the most active against clinical isolated Staphylococcus aureus MRSA, showing that structural requirements as prenylation at position C-6 or C-8 and OH at positions C-5, 7, and 4′ are key to the antibacterial activity. The combination of 11 or 12 with commercial antibiotics synergistically enhanced the antibacterial activity of vancomycin, ciprofloxacin, and methicillin in a factor of 10 to 100 times against drug-resistant bacteria. Compound 11 combined with ciprofloxacin was able to decrease the levels of ROS generated by ciprofloxacin. According to docking results of S enantiomer of 11 with ATP-binding cassette transporter showed the most favorable binding energy; however, more studies are needed to support this result.